The specificity of iNOS expression indicators in the basal magnocellular nucleus of rats under early pathogenetic correction in experimental neurodestruction - M. V. Danukalo; Yu. M. Kolesnyk (Zaporožskij Medicinskij Žurnal)
Aim. To characterize iNOS expression indicators in the basal magnocellular nucleus of rats during early pathogenetic correction of neurodegeneration induced by intracerebroventricular colchicine administration.